ASPEK HUKUM DALAM PELECEHAN SEKSUAL DI TEMPAT KERJA - Siti Awaliyah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
Sexual harassment has wide meaning. It is from seeing someone in such a way, to physical abuse. Sexual harassment is susceptible occurred in workplace; coming from the employers and also other employees. Sexual harassment is very disturbing. Therefore, legal protection is crucial for employees. This writing is discussing kind of sexual harassment in workplace and legal protection on victims of sexual harassment.